Prymas Wyszyński - obrońca zakonów wobec prześladowań władz Polskiej Rzeczpospolitej Ludowej - Kaczmarek, Ewa (Wydział Teologiczny, UAM, 2011)
Po II wojnie światowej instalowano w Polsce system komunistyczny wrogi wobec religii i Kościoła. Prowadzona przez rząd polityka antykościelna zakładała miedzy innymi walkę z zakonami, która ostatecznie miała doprowadzić do całkowitej likwidacji życia zakonnego w Polsce. W tym celu wykorzystano cały wachlarz metod administracyjnych, prawnych i ekonomicznych. Próbowano pozbawić zakony możliwości realizacji własnych charyzmatów i przekonać społeczeństwo o bezużyteczności życia zakonnego. Prymas Wyszyński, jako głowa Kościoła w Polsce podjął się obrony zakonów przez złośliwą i wrogą polityką państwa. Jego działania zmierzały do zapewnienia rodzinom zakonnym choć minimum przestrzeni potrzebnej do funkcjonowania i realizacji charyzmatów. Troska o los zakonów była obecna zarówno w dokumentach dotyczących relacji państwo – Kościół wychodzących z sekretariatu Prymasa, jak i w jego osobistych spotkaniach z przedstawicielami najwyższych władz w państwie. Obok tych działań Kardynał Wyszyński podjął prace zmierzające do podniesienia poziomu życia duchowego w zgromadzeniach i konsolidacji wszystkich zakonów w Polsce. Wielokierunkowa działalność Prymasa Wyszyńskiego i jego wielki autorytet sprawiły, że życie zakonne w Polsce Ludowej przetrwało czas prześladowań i wyszło z tej walki umocnione.

After World War II the Communist system hostile towards religion and the Church was installed in Poland. The anti-Church policy implemented by the government meant among other things struggle against religious orders with the aim of a complete elimination of religious life in Poland. For this purpose a wide range of administrative, legal and economic methods were used. There were attempts to deprive religious orders of the opportunities to carry out their charisms and to convince the society of the usefulness of religious life. Primate Wyszyński, as head of the Church in Poland committed himself to the defense of religious orders against the malicious and hostile policy of the government. His activity aimed at ensuring religious orders with at least a minimum space needed to live and to realize their charisms. His concern for the future of religious orders was present both in documents regarding the state - Church relations dispatched from the Primate's office and in his personal meetings with representatives of the highest authorities in the country. In addition, Cardinal Wyszyński took action towards improvement of spiritual life in religious congregations and consolidation of all religious orders in Poland. Primate Wyszyński's extensive activity as well as his great authority enabled religious life to survive the time of persecution in the People's Republic of Poland and to weather the struggle strengthened.
Primate Wyszyński - a Defender of Religious Orders against Persecutions by State Authorities in the Polish People's Republic
Keywords: prymas; primate; prześladowania; religious orders; zakonnice; nuns; polityka; policy; rząd; government